2017
DOI: 10.1177/1049732317721698
|View full text |Cite
|
Sign up to set email alerts
|

Why Should We Use Online Research Methods? Four Doctoral Health Student Perspectives

Abstract: The growth of the internet has led to an increase in researchers utilizing online methods. Online communities such as forums, blogs and video platforms are particularly useful for research involving populations that are internet savvy, seldom heard or discussing sensitive or illicit behavior. Drawing upon the experiences of four doctoral health students who are using online methods, this article discusses the value and benefits of conducting online research as well as the limitations and difficulties encounter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 19 publications
0
18
0
1
Order By: Relevance
“…However, identifying the range and content of topics discussed in online settings may help researchers to frame subsequent research. A caution in using extant data from the internet was described in recent work by Germain et al (2017). They found that it was possible to reidentify people by performing Google searches of specific quotes.…”
Section: Discussionmentioning
confidence: 99%
“…However, identifying the range and content of topics discussed in online settings may help researchers to frame subsequent research. A caution in using extant data from the internet was described in recent work by Germain et al (2017). They found that it was possible to reidentify people by performing Google searches of specific quotes.…”
Section: Discussionmentioning
confidence: 99%
“…We argue that such discussions are informative for understanding the specific contexts of status concealment given that such sensitive topics may be difficult to discuss with researchers. Online research is especially useful for the study of people or groups that may be hard to reach offline because they discuss “topics they may not feel comfortable sharing elsewhere” (Germain et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Illness stories published on the Internet are an emerging, valuable resource for health care research (Germain, Harris, Mackay, & Maxwell, 2017; Mazanderani & Powell, 2013; O’Brien & Clark, 2010) and constitute an underexploited database of patient-authored, patient journey representations. The advantages of these sources include that they are widely accessible, new contributions are regularly made to the database of stories, and the content is shaped by the events, thoughts, and feelings that are significant to the authors.…”
Section: Introductionmentioning
confidence: 99%